The Podsused reading rooms and library in the 20th century (Libellarium: journal for research in the field of information and related sciences, 2013)
The aim of the paper is to present the history of the Podsused reading rooms and library in the 20th century, using the original archival material. The materials stored in the Croatian State Archives, original printed and hand-written Regulations of reading associations, minutes of general meetings, and documents of other associations describe the organizational and operational features of reading rooms. In addition, private documents and photos of the citizens of Podsused were also used to reconstruct the operation and influence of the Susedgrad reading room on the life in Podsused. They recorded rich cultural activities of the reading association and its role in the cultural and public life of Podsused.The first readership associations were established in Podsused under the influence of the readership movement in Croatia: The Susedgrad reading room (1913), which was renamed in 1923 to the Croatian Reading Room of Podsused and the Croatian Reading Room Croatia in Podsused, located in the factory canteen of the Portland Cement Works (1923). The today's Library and Reading Room for Children and Adults was opened in 1951 in Dom kulture in Podsused, and has been working ever since.The main contribution of the paper is the identification of core features of the development of librarianship in Podsused in the 20th century.
Keywords: reading rooms; library; Podsused; Croatian Reading Room of Podsused; National Library and Reading Room Podsused; Vladimir Nazor Library